2006
DOI: 10.1212/01.wnl.0000230161.28299.3c
|View full text |Cite
|
Sign up to set email alerts
|

Lewy bodies in the amygdala increase risk for major depression in subjects with Alzheimer disease

Abstract: Lewy bodies (LBs) in the amygdala and in cortical areas increase the risk for major depression in Alzheimer disease. What is common in these two groups is the presence of LBs in the amygdala. That is, all of the cases with cortical LBs also had LBs in the amygdala, making this region the critical area for the development of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Samuels et al (2004) could not find cortical and subcortical Lewy body pathology associated with depression. In contrast, Lewy body density in the amygdalae was found to be associated with increased risk for major depression in subjects with AD (Lopez et al, 2006). Forstl et al (1992) explained the presence of depression in dementia by a loss of noradrenergic and cholinergic neurons in the Locus coeruleus and Nucleus basalis of Meynert.…”
Section: Discussionmentioning
confidence: 97%
“…Samuels et al (2004) could not find cortical and subcortical Lewy body pathology associated with depression. In contrast, Lewy body density in the amygdalae was found to be associated with increased risk for major depression in subjects with AD (Lopez et al, 2006). Forstl et al (1992) explained the presence of depression in dementia by a loss of noradrenergic and cholinergic neurons in the Locus coeruleus and Nucleus basalis of Meynert.…”
Section: Discussionmentioning
confidence: 97%
“…However, this pathology did not occur in isolation, and all participants had evidence of either vascular or Lewy body pathology. Another study found higher rates of depression in individuals with comorbid AD and Lewy body pathologies compared to those with AD alone (Lopez et al, 2006). Despite the well-established relationship between LLD and vascular disease (Taylor et al, 2013), little is known about how vascular disease contributes to the pathologic basis of depression in dAD.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, at least 59% of AD patients have LBs, usually restricted to amygdala and sparing the neocortical regions, with their number increasing as the disease progresses [30]. Interestingly, the presence of LBs in the amygdala appears to increase the risk for major depression in AD by nearly 5-fold [31]. Furthermore, in AD subjects with similar severity of cognitive impairment at baseline and comparable Braak stages at autopsy, those with concomitant neocortical LB pathology (referred to as Lewy body variant of AD) generally have faster cognitive decline and accelerated mortality compared to those with “pure” AD [32].…”
Section: Introductionmentioning
confidence: 99%